If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + (x + 1) = x + 1 Reorder the terms: 2 + (1 + x) = x + 1 Remove parenthesis around (1 + x) 2 + 1 + x = x + 1 Combine like terms: 2 + 1 = 3 3 + x = x + 1 Reorder the terms: 3 + x = 1 + x Add '-1x' to each side of the equation. 3 + x + -1x = 1 + x + -1x Combine like terms: x + -1x = 0 3 + 0 = 1 + x + -1x 3 = 1 + x + -1x Combine like terms: x + -1x = 0 3 = 1 + 0 3 = 1 Solving 3 = 1 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 16=3x+2x+1 | | -2.1(-3.2x-4)+1.2(2x-5)= | | 18x^5y^4/12x^-3y^-3 | | -7*9-9y=63 | | -15+65x= | | -2k+4-11=-8-6k | | m+6m=42 | | -4+2x=3-5x | | 2u+9=29 | | 2=y*2 | | 4z-6z-7= | | 77=5y+12 | | -7m+7=-14 | | m(3.14)=3 | | 9*(4*8+10)+2= | | x+-8=35 | | .33(6x-9)=-1.5(4x-5) | | d^3-24d=-2d^2 | | 20+7m=5+10m | | d^3-24d=-2d^2 | | .33(6x-9)=-1.5(4x-5) | | d^3-24d=-2d^2 | | 7[6-y]=-3[y-2] | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 |